IMPLIKASI HUKUM PEMUTUSAN HUBUNGAN KERJA ATAS PELANGGARAN HAK-HAK NORMATIF YANG DITIMBULKAN OLEH PERUSAHAAN OTO MULTIFINANCE: Legal Implications of Termination of Employment for Violation of Normative Rights by Company OTO MULTIFINANCE - Nabila Putri Insyani; Adityaningrum, Narita (Faculty of Law, Universitas Trisakti, 2025)
Termination of Employment is due to circumstances that have arisen, resulting in the termination of all rights and obligations between the employee and the employer. The implication of PHK in this case is the elimination of rights and obligations arising from the employment relationship between workers and employers. The action of PT. OM to unilaterally stop payment of wages is concluded that the employer is trying to end the employment relationship by violating regulations on employment. The consideration of the Panel of Judges; PT OM has not paid wages to C.I and friends for December 2010, January 2021 and February 2021. The formulation of the problem in this study is whether the normative rights received by C.I and friends are in accordance with Law Number 13 of 2003? The research method is normative and descriptive analytical, secondary data and deductive conclusion drawing. The results of the discussion and conclusion are that the normative rights received by C.I and friends are not in accordance with the decision, because in the case, the decision granted some of the demands of C.I and friends, which means there are normative rights that have not been fulfilled by PT. OM.